Implementasi Infak Produktif Dalam Pengembangan Ekonomi Keluarga (2020-2021) Di BMT Al-Hidayah, Kotaraja - Muhammad Iswandi, Lalu; Hasanah, Hidayatul (Al-Qardhu, 2024)
This research is motivated by the fact that the economic crisis experienced by the Indonesian nation has increased the number of poor people. Their number has increased over time along with the current decline in the national economic conditions. One effort to improve the economic welfare of the community is to maximize the potential of institutions that have been regulated by Islamic teachings, such as zakat, infak, and shadaqah. The purpose of this study is to determine the effect of productive infak on building the local economy. The data collection method is carried out using 3 methods that are often used in qualitative research for data collection, namely observation, interviews and documentation. The data obtained is then processed by collecting research data through three stages, including the preliminary stage, the filtering stage and the stage of completing data that is still lacking. The methods used are increasing perseverance, triangulation and open discussion. The data analysis in this study uses the stages of data collection, data reduction, data presentation and drawing conclusions. The results of the study indicate that the management of productive alms at BMT Al-Hidayah Kotaraja is good and has been in accordance with sharia provisions, so that the productive alms funds at BMT Al-Hidayah are felt to be beneficial by the community, especially the recipients of productive alms assistance funds as the purpose of BMT in improving physical and spiritual welfare is implemented without an interest system in BMT providing various assistance and training as well as providing business financing for small entrepreneurs. So that they are able to run independently and can open up job opportunities for the people, especially recipients of productive alms assistance funds, this explains that there is an influence of the Implementation of Productive Alms in developing the family economy